Representation of the Motives of Emigration of Modern Russian Youth among Smolensk Students - Valentina V. Gritsenko; Nadezhda V. Murashchenkova; Maria N. Efremenkova (Saratov State University, 2020)
The study of emigration intentions of young students is extremely relevant and is due to the need to solve an important social problem - preservation of human capital within the country, concern for the well-being of young people as the most active and educated part of the population. The purpose of the study is to identify the representation of Smolensk students jf the motives of emigration among Russian young people. The study is exploratory in nature and is focused on finding the answer to the following question: what are the motives for emigration behavior of modern Russian youth? The analysis of students' perceptions of emigration motives of their peers, on the one hand, allows us to assess the degree of comfort, safety and satisfaction of living environment in the country and, on the other hand, given the high probability of manifestation of the transfer and projection mechanism in answers, indirectly determine the dominant motives of potential emigration of students. The study was carried out on a sample (N = 255) of students from four Smolensk universities (aged 17 to 24 years old; 119 young men (47%) and 136 young women (53%) using the questionnaire designed by the authors. Methods of processing primary data - frequency and content analysis. As a result of a content analysis of students' perceptions of the motives of the emigration behavior of Russian young people, 6 main groups of motives were identified, which are based on the following factors: economic, political, legal, environmental, subjective and vital. These motivators are analyzed from the position of belonging to the attractive, expellant and individual-personal motives of emigration. The results obtained will help to expand specialists' understanding of psychological causes of young people's emigration behavior and can be used in the process of providing psychological assistance and support to potential emigrants.